Challenges in predicting risks of premature coronary artery disease (PCAD) - Muhammad Faizan A. Shukor,; Noor Akmal Shareela Ismail,; Wan Zurinah Wan Ngah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Coronary artery disease (CAD) predominantly manifests in older population above the age of 60 years old. The incidence of CAD in younger individuals has been reported and is called premature CAD (pCAD). The prevalence for pCAD in individuals below 45 years old is about 3-10% worldwide. Advances in risk prediction are of great importance as absolute values of risk factors sometimes correlate poorly with individuals. The measurement of traditional risk factors such as cholesterol level and blood pressure might be inadequate to predict risk for pCAD and therefore new biomarkers are required. The introduction of omics technology offers insight into the mechanism and interactions involved during disease progression and open the possibilities of discovering new biomarkers. Currently, new potential biomarkers for pCAD have been explored such as homocysteine, apolipoproteins, microRNAs and single nucleotide polymorphisms. In this review, we discussed the associated risk factors for pCAD, several reported and newly proposed biomarkers and their potential to be used clinically.